PERANCANGAN DAN FABRIKASI MESIN PERONTOK BIJI JAGUNG BERKAPASITAS 400 KG/JAM - Muhamad Khadafi (2023)
Corn (Zea mays L.) is a herbaceous plant and has a single seed (monocot). Corn is a vigorous, slightly clumped grass with rough stems and ranges from 0.6-3 m in height. Corn plants are a seasonal plant species with an age of ± 3 months. Threshing of corn kernels in home industries or small industries is mostly done in the traditional way. Then a corn thresher machine manufacturing process was carried out using research methods that began with concept design, manufacturing analysis, manufacturing processes, and trials that aimed to overcome the problems of corn processing, namely by making a corn thresher machine that could shell corn into round shells that can be used as fodder for livestock. After the manufacturing process was carried out, a thresher was produced which had overall dimensions of 62 cm x 45 cm x 45 cm which used an electric motor powered by 1.5 hp with a rotation of 2800 rpm as the driving force which after testing the thresher machine was able to produce 400 kg of corn kernels /hour Corn becomes ideal husks so that these husks can be used as feed for livestock.